2005
DOI: 10.1074/mcp.m500015-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Post-translational Modification of Nuclear Co-repressor Receptor-interacting Protein 140 by Acetylation

Abstract: Receptor-interacting protein 140 (RIP140) is a versatile co-regulator for nuclear receptors and many transcription factors and contains several autonomous repressive domains. RIP140 can be acetylated, and acetylation affects its biological activity. In this study, a comprehensive proteomic analysis using liquid chromatography-tandem mass spectroscopy was conducted to identify the in vivo acetylation sites on RIP140 purified from Sf21 insect cells. Reporter assays were conducted to examine the effects of acetyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
49
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 42 publications
2
49
0
Order By: Relevance
“…Through extensive mass spectrometric analyses, we found RIP140 are extensively phosphorylated (28) and acetylated (29). To continue the functional proteomic endeavor, we took a systematic mutagenesis approach to uncover the function and the mechanism of actions of specifically modified residues of RIP140.…”
mentioning
confidence: 99%
“…Through extensive mass spectrometric analyses, we found RIP140 are extensively phosphorylated (28) and acetylated (29). To continue the functional proteomic endeavor, we took a systematic mutagenesis approach to uncover the function and the mechanism of actions of specifically modified residues of RIP140.…”
mentioning
confidence: 99%
“…Moreover, because certain modification sites clearly deviate from the consensus, other factors, such as subcellular environment, local concentration of E3 SUMO ligase activity and/or other covalent modifications, must influence the modification and affect the target site specificity (22). Interestingly, the Lys 111 of RIP140 appears to be acetylated in vivo (17), which may explain its lack of SUMOylation. Overexpression of SUMO E3 ligases PIAS1 and PIAS3 that promoted SUMO-1 modification of wild type RIP140 also brought about weak SUMO-1 modification of the RIP140K756R,K1154R mutant, suggesting that secondary sites, such as Lys 170 , can become SUMOylated under conditions promoting the modification.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, arginine methylation at Arg 240 , Arg 650 , and Arg 948 was shown to weaken the corepressor activity because of attenuated recruitment of HDACs and increased nuclear export (16). Huq and Wei identified four acetylation sites in RD1 and three in RD2, and their experiments with an HDAC inhibitor suggested that hyperacetylation enhances the repressive activity of RIP140 (17). According to another study, acetylation of Lys 446 within the N-terminal CtBP-binding motif reduces its interaction with CtBP, thereby attenuating transcription repression by RIP140 (13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Site-directed mutagenesis studies demonstrated the functionality of phosphorylation on Ser 19 and Ser 68 but not Ser…”
mentioning
confidence: 99%